(Re)prezentacija beogradskog novog talasa u romanu Kada kažeš da sam tvoj - Ajduk, Marija (Etnoantropolos̆ki problemi, 2025)
The New Wave movement in rock and roll music represents a significant phenomenon within the local (Yugoslav) context. Its impact on the perception of both the past and the present is reflected in the continuous and increasingly pronounced need to organize tributes in the form of concerts, exhibitions, panel discussions, documentary films, and novels. This paper presents an anthropological analysis of the novel When You Say That I Am Yours (Kada kažeš da sam tvoj) by the writer Goran Skrobonja. The novel is set in the second half of the 1980s, during the existence of the Socialist Federal Republic of Yugoslavia. The main protagonist, Lazar Petronijević, lives and grows up in Belgrade and belongs to the ‘New Wave’ rock and roll scene that emerged in the early 1980s and continued to exert its influence in various forms throughout the decade. The aim of this research is to reconstruct the meanings attributed to the New Wave movement, the music scene of the time, and the city of Belgrade during that period, meanings that are shaped through memory and personal narratives. One of the conclusions drawn from the analysis is that the reality presented in the novel largely corresponds with the kind of (New Wave) reality that is frequently discussed, written about, filmed, and continuously reproduced as the ‘everyday life of the 1980s in Yugoslavia’. The novel's analysis also reveals that although the term New Wave is not explicitly mentioned in many instances, it is deeply embedded in various meaningful elements identified in the text, such as descriptions of the city, public and private gathering places, radio and television shows, and magazines. These elements, which form the basis of the socialization process centered around music, not only create a symbolic network of meanings that shape the daily life of Lazar Petronijević but also ‘bring back’ to the 1980s a particular generation of readers, to the time of their youth, allowing them to evoke memories while simultaneously constructing retrospective meanings that transcend individual experiences and evolve into shared cultural representations, thus making them anthropologically relevant.